Hydrides for energy storage proceedings of an international symposium held at Geilo, Norway, 14-19 August 1977 - Andresen, A. F.; Maeland, A. J. (Pergamon Press, 1978)
Hydrides for Energy Storage documents the proceedings of an International Symposium held in Geilo, Norway on August 14-19, 1977. This book discusses the thermodynamics of metal, alloy and intermetallic/hydrogen systems; localization and diffusion of hydrogen in lanthanum-nickel compounds; kinetics of hydrogen absorption and desorption; and nuclear magnetic resonance studies of metal hydrides. The calculated heats of formation of metal and metal alloy hydrides; hydrogen absorption into rare earth intermetallic compounds; plateau pressure of RE Ni5 and RE Co5 hydrides; and hydride formation of C14-type Ti alloy are also elaborated. This text likewise covers the mixing effects of two different types of hydrides; hydrogen storage electrode systems; and applications of metal hydrides. This publication is intended for chemists concerned with the fundamental properties of hydrides.--Provided by publisher.